Evaluating the Benefits of New Financial System (Accrual Accounting) Establishment in Medical and Health Care Sciences, Guilan University - Mohammad Reza Pour Hosein; Morteza Hassanzadeh; Seyedeh Saeedeh Hashemi (International Journal of Economics and Financial Issues, 2017)
The purpose of present study is assessing the benefits of accrual accounting establishment in Guilan Medical Sciences University during 2008-2012. This research is a field and scaling survey. Approximately 86.1% of respondents agreed with performing the accrual accounting and had a positive view about its benefits. Research results showed that performing of accrual accounting in Guilan Medical Sciences University can express the total cost of services and activities more clearly and facilitate to perform operational budgeting. Extracted data from this system can help managers in optimum responding and decision making. Finally it was clarified that the value of output data from accrual accounting system in the university is more than the establishment cost of it. Considering the proportional faults of accrual accounting because of having more benefits in comparison with cash basis, performing this system in reporting and financial affairs of Guilan Medical Sciences University leads in not only benefiting from other innate advantages of accrual accounting, but also provides required conditions in the area of changing current university budgeting into operational budgeting and results in achieving organizational goals.